Pharmacokinetics of iodine-123-IMBA for melanoma imaging - Nicholl, Ciaran; Mohammed, Ashour B.; Hull, William Edmund; Bubeck, Bernd; Eisenhut, Michael (Journal of nuclear medicine, 1997)
The development of an effective radiopharmaceutical with affinity for malignant melanoma has been a research goal for some time. The early detection of melanoma metastases would greatly improve the therapy outcome for this disease. This article describes the synthesis of radioiodinated IMBA, N-(2-diethylaminoethyl)-3-[123I/131I]iodo- 4-methoxybenzamide 8, its organ distribution, its comparison with BZA and other benzamides, and demonstrates the scintigraphic efficacy of the title compound with three melanoma patients. Methods: The syntheses and radioiodination of eight benzamide derivatives are described. After intravenous injection into C57BI 6-mice subcutaneously transplanted with B16 melanoma, the organ distribution of the respective benzamides were investigated at 1 and 6 hr. n-octanol/phosphate buffer partition coefficients. The whole-body retention, erythrocyte and serum protein bound fractions of radioiodinated benzamides were measured. Results: While structural changes in the amide substituents of N-(2-dialkylaminoalkyl)- 4-iodobenzamides 2-7 resulted in no improvement in organ distribution compared with BZA, the 3-iodo-4-methoxyphenyl form of IMBA showed high melanoma uptake with significantly higher melanoma/nontarget tissue ratios. Compared with BZA the average ratio improved after 1 hr by a factor of eight and was still four times better after 6 hr. BZA and IMBA exhibit almost identical n-octanol/phosphate buffer partition coefficients, however, IMBA has a faster urinary excretion facilitated by a lower affinity to erythrocytes and serum proteins; this could explain the improved tissue partinioning observed. Scintigraphy of patients with melanoma metastases confirmed the promising characteristics derived from the animal studies Conclusion: Due to rapid background clearance and high melanoma affinity, IMBA showed high tumor contrast already at 4 hr after injection which makes it a promising new radiopharmaceutical for the scintigraphic detection of melanoma metastases.